2006
DOI: 10.1038/sj.onc.1209564
|View full text |Cite
|
Sign up to set email alerts
|

Proline oxidase activates both intrinsic and extrinsic pathways for apoptosis: the role of ROS/superoxides, NFAT and MEK/ERK signaling

Abstract: Proline oxidase (POX), often considered a 'housekeeping enzyme' might play an important role in apoptosis. We have shown that POX generated proline-dependent reactive oxygen species (ROS), specifically superoxide radicals, and induced apoptosis through the mitochondrial (intrinsic) pathway. In our current report, we used DLD-1 colorectal cancer cells stably transfected with the POX gene under the control of a tetracycline-inducible promoter and found POX-stimulated expression of tumor necrosis factor-related a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
165
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(169 citation statements)
references
References 36 publications
4
165
0
Order By: Relevance
“…These results also suggested that both O 2 •-and hydroperoxides were capable of contributing to the oxidative stress and cytotoxicity seen during 2DG and Adp53 treatment. These results are also consistent with the previous observations that p53-dependent apoptosis was preceded by the induction of the enzyme proline oxidase and increased respiration presumably leading to the increased generation of O 2 •-and hydroperoxides [9,10,20,36].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results also suggested that both O 2 •-and hydroperoxides were capable of contributing to the oxidative stress and cytotoxicity seen during 2DG and Adp53 treatment. These results are also consistent with the previous observations that p53-dependent apoptosis was preceded by the induction of the enzyme proline oxidase and increased respiration presumably leading to the increased generation of O 2 •-and hydroperoxides [9,10,20,36].…”
Section: Discussionsupporting
confidence: 93%
“…Recent reports also documented that the combination of ionizing radiation and adenoviral p53 gene therapy increased radiosensitivity of both p53-mutant and wild type cancer cells [7;8;35]. In addition several reports have suggested that p53 over expression can induce oxidative stress and alterations in respiration in cancer cells [1,2,9,10,20,36] and that 2DG can enhance cell killing in malignant cells by agents that induce metabolic oxidative stress [3,4,37]. Finally, several investigators have reported that androgenindependent prostate cancer cells have a high frequency of p53 mutations [38;39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…P5C is then converted to glutamate in a NAD + -dependent reaction catalyzed by P5CDH [2]. Phang and others have shown that in mammalian cells PRODH expression is activated by p53 with proline oxidation leading to increases in intracellular reactive oxygen species (ROS) and induction of cellular apoptosis in various cancer cell lines [3][4][5][6][7][8][9]. Thus, proline serves as a prooxidant in apoptotic signaling via PRODH activity which may be an important mechanism for reducing carcinogenesis [6].…”
Section: Introductionmentioning
confidence: 99%